Celular concentration and dry biomass in three species of marine microalgae: Chlorella vulgaris, Nannochloropsis oculata and Tetraselmis striata - Méndez Ancca, Sheda (2020)
The aim of study was to determine cell concentration and dry biomass in three species of marine microalgae: Chlorella vulgaris, Nannochloropsis oculata and Tetraselmis striata. The strains were supplied by the Ilo Coastal Laboratory belonging to the Peruvian Institute of the Sea (IMARPE) and then, the microalgae were conditioned to be cultivated in a semi-controlled medium. The phases of the microalgae culture consisted of the cepario, initial, intermediate and massive. The order of maximum cellular concentration (cel/mL) for the microalgae was Nannochloropsis oculata > Chlorella vulgaris > Tetraselmis striata where N. oculata represented 7.63 times higher than T. striata. In the case of biomass, the order corresponded to: C. vulgaris > T. striata > N. oculata, with a 1.32 g difference. It was concluded that the microalgae species Chlorella vulgaris indicated the greatest advantage to be used in aquaculture compared to the other two species.